Systems of national accounts in Africa - Ady, Peter H.; Courcier, Michel; Commission for Technical Co-operation in Africa South of the Sahara ([Paris] Organisation for European Economic Co-operation, 1960)
The book explains the use of national accounts in describing and analyzing of economic systems.
"Corrigenda" leaf inserted.
gp. 21/01/2019
Loans
Keywords: Income; National accounts; Africa